2014
DOI: 10.1007/s12328-014-0486-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between autoimmune pancreatitis and malignancy

Abstract: Chronic inflammatory diseases are often associated with malignancy, and this phenomenon occurs even in the field of gastroenterology. For example, chronic pancreatitis has been reported to be highly associated with the occurrence of pancreatic cancer. However, the association between autoimmune pancreatitis (AIP) and pancreatic cancer is still an unsolved problem. As AIP is associated with immunoglobulin G4-related disease, which causes a variety of inflammatory and fibrotic lesions, the association between AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The definite association between AIP and PaT remained inconclusive. Some researchers have suggested that AIP may be a manifestation of paraneoplastic syndrome [10, 16], some have indicated that chronic pancreatic inflammation in AIP may contribute to carcinogenesis [8, 12, 19], and some have reported that AIP was not associated with an increased incidence of total malignancies [20, 21]. Our results tended to support the hypothesis of paraneoplastic syndrome, which would be briefly explained below.…”
Section: Discussionsupporting
confidence: 82%
“…The definite association between AIP and PaT remained inconclusive. Some researchers have suggested that AIP may be a manifestation of paraneoplastic syndrome [10, 16], some have indicated that chronic pancreatic inflammation in AIP may contribute to carcinogenesis [8, 12, 19], and some have reported that AIP was not associated with an increased incidence of total malignancies [20, 21]. Our results tended to support the hypothesis of paraneoplastic syndrome, which would be briefly explained below.…”
Section: Discussionsupporting
confidence: 82%
“…It could be because IgG4-RD causes sustained inflammation that may induce preferable cancerous microenvironments, which resembles the mechanism of lymphoma development in association with Sjögren's syndrome 28 . However, it has been reported that surgical resection of cancer was able to cause remission of IgG4-RD 25,29 , indicating that IgG4-RD might be a type of paraneoplastic syndrome 1 . Overall, it is still too early to draw a definitive conclusion of the pathogenesis of IgG4-RD and malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the aim of Hirano's study was to clarify the oncogenic effects in the presence of established IgG4-RD, they tried to address whether preceding IgG4-RD and/or type 1 AIP could cause malignant disorders. Therefore, the discrepancy between Shiokawa's and Hirano's studies can be partially explained by the fact that significant numbers of cases with concurrent cancer and AIP were included in the former study (10) whereas such cases were excluded in the latter study (12,17). Consistent with this idea, the SIR for cancer was much lower in cancer cases detected at more than one year after the diagnosis of AIP than in those detected within one year (10).…”
Section: Incidence Of Cancer In Igg4-rd and Aipmentioning
confidence: 95%
“…Although the reasons for such discrepancy have not been fully elucidated, two possibilities have been discussed (12,17). One possibility is related to dealing with patients in whom cancer and AIP occur concurrently.…”
Section: Incidence Of Cancer In Igg4-rd and Aipmentioning
confidence: 99%